Effects of a soccer tournament on the psychohormonal states of collegiate female players - Broodryk, A.; Pienaar, C.; Edwards, D.; Sparks, M. (The Journal of Strength and Conditioning Research, 2021)
A gap exists in the literature concerning the connection between soccer players' hormonal and psychological responses when playing a tournament, or even a match, and its outcome (victory or defeat). This study evaluates the effects of a week-long tournament on the psychohormonal states of collegiate female soccer players. Eight players' cortisol (saliva sample), mood states (Incredibly Short Profile of Mood States [ISP]), and state-anxiety (state subscale of the State-Trait Anxiety Inventory) were assessed 1 hour before and 15 minutes after every game. Cortisol increased significantly after most matches, with intramatch differences observed (p < 0.05, d > 1.2). Match intensity influenced cortisol secretion, with greater secretion as intensity increased. The ISP demonstrated intramatch differences for the subscales' fatigue, depression, tension, and vigor (p < 0.05). Matches lost produced a higher total mood disturbance (TMD) index compared with matches won (p = 0.001, d = 1.4). Cortisol correlated with the TMD and various mood subscales before a winning outcome, with the ISP correlating at all times with the anxiety scores (p < 0.05). In conclusion, these results indicate that physiological and psychological variables combine to contribute to the stress response during a tournament. Focusing on high-intensity activities and minimizing fatigue are important, as both are associated with raised cortisol and negative mood states. Finally, implementing a mood questionnaire over a tournament can be beneficial, as sensitive information on players' hormonal and perceived anxiety states, which subsequently affect physical performance, can be obtained.